Biomechanics of the Cross-Country Sit-Skier and impact on Sit-Ski Design - a Top Secret 2010 Project - Leblanc-Lebeau, M.; Rancourt, D.; Langelier, E.; Cyr, M.; Lessard, J.; Smeesters, C. (34th annual meeting of the American Society of Biomechanics at Brown University Providence, Rhode Island on August 18 - 21, 2010 - Poster 315, 2010)
In paralympic cross-country skiing, athletes compete in one of three categories: visually impaired athletes compete with an able-bodied guide and use 2 skis and 2 poles; standing athletes compete using 2 skis and 0, 1 or 2 poles; and sitting athletes compete on a sit-ski with 2 skis and use 2 poles. Even within each category there is a wide range of disabilities, for example, from complete impairment of the lower limbs and minimal trunk muscle activity for LW10 sitting athletes, to only partial impairment of the lower limbs and normal trunk muscle activity for LW12 sitting athletes. Actual race time is thus multiplied by a percentage factor dependent on disability and the skier with the lowest calculated race time within each category is the winner. Furthermore, disability obviously affects the muscle power produced by the athlete to increase and maintain speed, but for sit-skiers it also uniquely affects their ability to negotiate turns. An LW12 sitskier can lean toward the inside of a turn to increase the centripetal force and thus avoid tipping over toward the outside of a turn. However, an LW10 sitskier is physically unable to lean into a turn and can only avoid tipping over toward the outside of a turn by using his outside pole to push himself toward the inside of a turn. Their only other option is to slow down to negotiate turns, which is not the best strategy if they want to win a race. The completely rigid structure of current sit-ski designs makes negotiating turns especially difficult. Indeed, whether it is because they undercompensated or over-compensated for a turn, sitskiers will often find themselves precariously balancing on only one ski during turns, narrowly avoiding tipping over toward the outside or the inside of the turn. The purpose of this project was thus to improve sit-ski design to make it more stable and more agile during turns. To do so we studied the effect of adding a tilting mechanism to the sitski on maximum allowable turning velocities.